Formate addition enhanced hydrogen production by Thermococcus paralvinellae when grown on brewery wastewater - Sistu, Harita; Holden, James F. (Frontiers in Microbiology, 2025)
The hyperthermophilic archaeon Thermococcus paralvinellae produces H2 when grown on carbohydrates or protein with increased H2 production when cultures are grown on formate. This study examined the use of brewery wastewater as a feedstock for H2 production, the addition of formate to enhance H2 production, and the activities of hydrogenases and formate hydrogenlyase under varying growth conditions as markers of performance. T. paralvinellae was grown at 80°C on maltose only (a model brewery wastewater), formate only, and maltose plus formate media as well as brewery wastewater with and without the addition of formate. Growth rates were higher on formate only medium than on maltose only and brewery wastewater only media. H2 yield per cell was higher in all media containing formate relative to those without formate. Hydrogenase and formate hydrogenlyase specific activities were not affected by the presence of formate and were largely consistent across all growth conditions. Growth rates were consistent in media containing 0.05 to 2.5% (wt/vol) maltose only, but total H2 production doubled from medium containing 0.05% maltose to 0.5% maltose and remained unchanged at higher maltose concentrations. Cells grown in a 2 L N2 flushed batch bioreactor at 80°C on brewery wastewater with and without formate showed no difference in growth rates but the amount of H2 in the headspace was six times higher when formate was present. However, the amount of H2 produced by cells grown on brewery wastewater plus formate peaked in mid-logarithmic growth phase and then decreased to amounts produced by cells without formate addition by late logarithmic growth phase. When the bioreactor was run as a chemostat, the addition of formate to brewery wastewater led to a 12-fold increase in the amount of H2 present in the headspace that was sustained over time relative to growth without formate addition. Therefore, T. paralvinellae grows on brewery wastewater as its sole source of organic carbon and produces biohydrogen at a steady rate in a pilot-scale bioreactor, and H2 production is enhanced by formate addition.